The Impact of Exploitative working relationships on employees’ health and behaviors - Costa, S.; Jacqueline A.-M. Coyle-Shapiro; Corlett, S.; Aguiar, T. R. (1st Annual Poster Blitz in Psychology of Health and Wellbeing, 2025)
Recent research argues that exploitative working relationships can be present in any context and experienced by any employee, but its prevalence is unknown. We expand the theory of the effects of employees’ perceptions of exploitation by proposing and testing key processes (emotional, cognitive, and motivation) and outcomes (burnout, depressive symptoms, and somatic complaints). Specifically, we suggest that negative emotions, effort-reward imbalance, and thwarted psychological needs are intertwined mechanisms linking perceived exploitation to health-related outcomes. We aimed to empirically test these claims, through three separate studies employing various methodologies. In study 1, we took a qualitative approach to collecting information on the various perceptions of exploitation. In study 2, we used both time-lagged measures and an experimental design to test the relationship between perceived exploitation and other key constructs used in the study of employee welfare. Finally, in study 3 (still in development), we use Fitbit technology and a diary study design to track the weekly fluctuations of both physiological and perceived employee welfare. Overall, our results support the claims previously proposed in the literature and call for further study on this topic.